Proposal of a methodology for the performance of functional and clinical testing of medical devices designed and manufactured by covid 19, through the use of informed consent - Auccahuasi, Wilver (2020)
ABSTRACT The effects of the pandemic caused by COVID-19, are causing the development of medical implements and equipment quickly, in some cases due to the emergency situation authorizations are being granted for the manufacture, marketing and use. In many cases these developments are motivated by a local need that can help mitigate the effects of COVID-19. It is in this scenario, where we present a methodology to be able to collaborate in that these developments, providing recommendations of good practices for the functional testing stage, based on the design of the test protocols and informed consent, with these testing mechanisms, are It can be presented to a health ethics committee, with the intention that it be approved for subsequent application. With the completion of the studies using the equipment developed and having passed the study protocol, the results of the study guarantee that the equipment developed can be approved for registration, commercialization and subsequent clinical use. The use of the study protocol with the informed consent helps in the clinical tests of the device, the regulatory requirements must be taken into consideration for the development of the equipment that ensures the safety and integrity of the patients when they use the medical devices.. The results presented are based on the considerations to be taken into account at the time of writing the study protocols and the respective informed consents.